2007
DOI: 10.1021/ma071337p
|View full text |Cite
|
Sign up to set email alerts
|

Toward Controlled Gilch Synthesis of Poly(p-phenylene vinylenes):  Anionic vs Radical Chain Propagation, a Mechanistic Reinvestigation

Abstract: It is a broad consensus that the first step in the Gilch synthesis of poly(p-phenylene vinylenes) (PPVs) is 1,6-dehydrohalogenation of the 1,4-bis(halomethylene)benzene starting materials. The mechanism of the subsequent chain growth of the resulting R-halo-p-quinodimethane monomers, however, is still a matter of discussion. We re-evaluated the arguments presented for anionic chain propagation and set them against the evidence obtained for a radical mechanism. We conclude that (i) the initial dehydrohalogenati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 51 publications
(118 reference statements)
3
61
0
1
Order By: Relevance
“…In order to keep the NMR spectra as simple as possible, we avoided aromatic substituents and focused our investigations on 5-methoxy-2-(b-ethylhexyloxy)-1,4-bis(chloromethylene)benzene 1a and 2,5-bis(bethylhexyloxy)-1,4-bis(bromomethylene)benzene 1b as the standard starting materials (Figure 2). [64,65,67] For comparison purposes, their 2,5-dihexyloxy-substituted (1c) and 2,5-bis(b-ethylhexyl)-substituted counterparts (1d) were also tested in some experiments, which bear linear and oxygen-free solubilizing side chains, respectively. The alkyloxy-substituted starting materials are easily available by the treatment of either hydroquinone 5 or hydroquinone monomethyl ether 6 with the corresponding alkyl bromide and potassium hydroxide, followed by the introduction of either two chloromethylene or two bromomethylene functional groups through twofold halomethylation (Scheme 5).…”
Section: Standard Starting Materials and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to keep the NMR spectra as simple as possible, we avoided aromatic substituents and focused our investigations on 5-methoxy-2-(b-ethylhexyloxy)-1,4-bis(chloromethylene)benzene 1a and 2,5-bis(bethylhexyloxy)-1,4-bis(bromomethylene)benzene 1b as the standard starting materials (Figure 2). [64,65,67] For comparison purposes, their 2,5-dihexyloxy-substituted (1c) and 2,5-bis(b-ethylhexyl)-substituted counterparts (1d) were also tested in some experiments, which bear linear and oxygen-free solubilizing side chains, respectively. The alkyloxy-substituted starting materials are easily available by the treatment of either hydroquinone 5 or hydroquinone monomethyl ether 6 with the corresponding alkyl bromide and potassium hydroxide, followed by the introduction of either two chloromethylene or two bromomethylene functional groups through twofold halomethylation (Scheme 5).…”
Section: Standard Starting Materials and Proceduresmentioning
confidence: 99%
“…[65] The intense, broad and unstructured absorptions represent the characteristic signature of the regularly trans-configurated repeating units of a highmolecular-weight PPV: at d % 7.1 and 7.5 ppm, one observes the signals of the phenylene and vinylene protons, at d % 3.9 ppm those of the OÀCH 2 protons, and above d 2.0 ppm appear all other protons of the lateral b-ethylhexyloxy substituents.…”
Section: Standard Starting Materials and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…In the sulfinyl route, a strong base is generally required to eliminate a leaving group from a precursor monomer to form a polymerizable quinodimethane system (see Scheme 1 for structure). Under most reaction conditions these quinodimethanes are unstable and undergo spontaneous radical polymerization (it should be noted that in older literature very often anionic polymerization conditions were erroneously postulated; newer studies indicate that radical polymerization is much more likely to occur) [9]. To switch from radical to anionic polymerization, the base employed in the in-situ-formation of the actively propagating monomer was changed from tert-butoxide to the more sterically hindered base LHMDS (lithium hexamethyldisilazide) while the solvent needs to be replaced by an aprotic solvent such as THF [21].…”
Section: Introductionmentioning
confidence: 99%
“…The solvent and base used seem to play an important role and depending on the materials used, the mechanism can be radical and/or ionic. In the case of THF as the solvent and potassium tert-butoxide (KO t Bu) as base, it was shown that the polymerization proceeds via a radical chain growth mechanism, as it was verified by using spectroscopic methods (UV-Vis, NMR, EPR spectroscopy) and a radical trapping agent [18,22,23]. In Scheme 1 the reaction mechanism of alkoxy substituted α,α´-dihalogenp-xylene 3 (premonomer) with KO t Bu is shown.…”
Section: Synthesis Ofmentioning
confidence: 99%